Percutaneous Endoscopic Discectomy via Transforaminal Route for Discal Cyst - Subash C. Jha; Kosaku Higashino; Toshinori Sakai; Yoichiro Takata; Mitsunobu Abe; Akihiro Nagamachi; Shoji Fukuta; Koichi Sairyo (Case Reports in Orthopedics)
Background. Discal cyst has been identified as a rare cause of low back pain and radiating leg pain. The pathogenesis and management of this condition are still debated. The largest number of reported cases had undergone microsurgery while very few cases have been treated with percutaneous endoscopic discectomy (PED). Methods. An 18-year-old boy complained of low back pain radiating to right leg after a minor road traffic accident. Diagnosis of a discal cyst at L4-L5 level was made based on magnetic resonance imaging (MRI). Despite conservative management for 6 months, the low back pain and radiating leg pain persisted so surgical treatment by PED was performed under local anesthesia. As the patient was a very active baseball player, his physician recommended a minimally invasive procedure to avoid damage to the back muscles. Results. The patient’s low back pain and leg pain disappeared immediately after surgery and he made a rapid recovery. He resumed mild exercise and sports practice 4 weeks after surgery. Complete regression of the cystic lesion was demonstrated on the 2-month postoperative MRI. Conclusion. A minimal invasive procedure like PED can be an effective surgical treatment for discal cyst, especially in active individuals who play sports.